Why Green IC does not Influence Firm Value? - Agustin, Fitri Devy; Augustine, Yvonne (Technium Social Sciences Journal, 2023)
The study’s objective is to examine the effects of green intellectual capital on Tobin's Q in relation to firm value calculations. The study took place during the period from 2019 to 2022. It focused on companies in Energy, Transportation and Logistics, and Industry listed on the Indonesia Stock Exchange’s main board. Secondary information from corporate financial statements and sustainability reports or annual reports are used in this research. A purposive sampling method was used for sample selection to obtain 183 observations and the test using multiple regression analysis. The study result shows that green human capital, green structural capital, and green relational capital do not influence firm value simultaneously. Companies must fully manage their intellectual capital with maximum attention to the environment to influence firm value.